Empathy and Motivations to study Medicine in University Students from Lima and Province - Acevedo-Flores, Jessica (2025)
Introduction: Empathy and motivations to study Medicine are important for the performance of the future doctor and for the quality of service provided. Objective: To establish the relationship between empathy and the social/altruistic and economic/prestige domains of the motivations to study medicine in university students of three Peruvian cities; also, to compare the correlations of the variables according to the sex of the students. Methods: Cross-sectional correlational design. The sample was made up of 249 students of both sexes, 166 women and 83 men, between the ages of 17 and 27, who were studying from the first to the seventh year of Medicine at a private university based in three Peruvian cities (Lima and Province). The instruments used were the Cognitive and Affective Empathy Test and the Motivations Scale to study Medicine. Results: The association between Altruistic Social Dominance (ASD) with Perspective Adoption (AP) and Empathic Joy (EA) was direct and significant for both groups, of medium intensity for women and strong for men. Furthermore, the association between DSA and Emotional Understanding (EC) was also direct and significant for both groups, with a strong intensity in the male group. Finally, the Prestige Economic Domain (DEP) presented significant positive associations of medium intensity with PA, CE and EA in men. Discussion: There are differences in the relationships established between the motivation to study medicine and empathy, according to sex...